Meyer’s Approach on Musical Analysis and Its Relevance to Indonesian Analytical Study of Western Music - Andre Indrawan (Institut Seni Indonesia Denpasar, 2020)
This critical review of Leonard Bunce Meyer's musical analysis theory is aimed at obtaining a basic understanding of an approach that seems uncommon in Indonesian studies of Western music. This study uses a speculative method with descriptive as well as critical approaches, where Meyer's analysis theory is depicted critically by conforming it toward Nicolas Cook's critical review which was based on the Shenkerian concept. The relevance application of this analysis model in the studies of musical form in Indonesia then is discussed. This study concluded that the psychological music analysis of Meyer was carried out by the foreground expectations of the tonal music linear and rhythmical analysis. Compared to the Shenkerian approach which gives greater attention to the harmonic reduction that focused on the harmonic background of tonal music, Meyer’s approach would be less practical in observing at large-scale musical structures. Meyer’s analysis would be valuable to the performers as well as music analysts if they also take into account their musical style concepts which mostly regarded as the area of aesthetic rather than technical analysis. For Indonesia, this method is appropriate for Master and Doctorate studies in Western Music.